An interview study of why parents conduct intensive ABA home training for their child with autism spectrum disorder. An analysis from the lens of the dialectical disability model. Issue 2 (3rd April 2017) - Ravn Andersen, Esther; Bøttcher, Louise; Dammeyer, Jesper
Abstract: The number of parents undertaking an intensive home training programme of children with disabilities (e.g. Applied Behavioural Analysis) has increased. It reveals a paradox in current disability research and policies. On the one hand, policies in general are aimed at inclusion through movement of social barriers for participation, grounded in the social model of disability. On the other hand, intensive home training is based on the aim of rehabilitation through intensive training of individual cognitive and social skills, an approach grounded in a bio-medical model. Intensive home training programmes are supported by political legislation that enables parents to partake the training and hire the necessary helpers. How is this paradox viewed from the perspective of the parents? From the departure of the dialectical model of disability – and its central concepts of developmental incongruence, developmental time and social agency – two mothers practising home training with their children with autism disorder were interviewed about their motives for home training and subsequent experience with their child. Results showed that the motive to home training was to create a local congruence that allowed the child to thrive. Intensive home training also restored the mothers' sense of agency vis-à-vis their child's development. However, home training might not abolish the need for adaptations of the child's social practices outside the family. It is discussed how societal support to home training risks to hinder higher order reorganisation of developmental opportunities that are necessary to actualise policy statements of inclusion.